LITERATURE: A MEDIUM FOR YOUNG LEARNERS TO UNDERSTAND OTHER CULTURES - Aisyah Shahab (HOLISTICS, 2020)
Abstract: Cultural understanding cannot be separated from language learning. It can improve thelanguage skills of language learners. Language teachers are suggested to teach not only thelinguistic knowledge but also the cultural knowledge and to provide the media which can helplearners to have better competence in using the language, in this case is English. One of the mediais literature. It will help students to have closer and better look on the cultures where English isused. This cultural understanding is important to be promoted at early age. Young learners are attheir best time in learning process, including in learning a culture through literature. This paperhighlights the importance of cross cultural understanding and literature as the medium in theprocess of teaching English to young learners.